Efektivitas Peran Pos Bantuan Hukum di Pengadilan Agama dalam Memberikan Layanan Hukum Kepada Masyarakat - Eneng Nuraeni; Riyan Ramdani (Khazanah Multidisiplin, 2025)
Legal aid is a human right recognized and protected for all legal subjects. This research aims to analyze the effectiveness of Posbakum services in several Religious Courts in West Java. This descriptive qualitative study uses data collection techniques such as observation, interviews, and documentation. The findings show that the service effectiveness is measured using Duncan's indicators: (1) Goal achievement, which is quite effective but faces challenges in time management; (2) Integration, which is not yet effective due to issues in the service process and limited socialization to remote areas; (3) Adaptation, which is moderately effective. Key supporting factors include collaboration with competent parties, adequate funding, and necessary facilities. Recommendations include expanding socialization efforts through outreach to remote locations, utilizing social media for information dissemination, and creating suggestion boxes for feedback. Furthermore, it is recommended to enhance staff capabilities through training, seminars, and workshops on legal aid services, improve time discipline, and ensure consistency in providing accurate court schedules and information to avoid inconvenience for the public. This research contributes to improving the quality of legal aid services, especially in terms of outreach and staff development, which is crucial for ensuring access to justice for all citizens.